ANALISIS DAN PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA DENGAN METODE PROFILE MATCHING PADA MAN 2 JAMBI: DSS, Scholarship, Profile Matching - Suana, Irma; Safar, M. (JURNAL AKADEMIKA, 2019)
Senior high school MAN 2 Jambi is one of the schools that already have a scholarship program that is given to students who excel and poor students. Scholarship programs undertaken by several agencies both government and non-government. To simplify the scholarship selection process in Senior high school MAN 2 Jambi, the author proposes a computer-based decision support system that can make the scholarship selection process is faster and the results obtained more accurate decisions, and minimize the level of subjectivity in the assessment. Decision Support System Acceptance Scholarship is built using profile matching method. Profile matching method chosen because it is able to select the best alternative of aspects - aspects of the existing criteria. The workings of profile matching method is to compare the value of the profile of the candidate grantee with the target value of the criteria established by Senior high school MAN 2 Jambi. The less the difference between the candidates with the target profile, the greater the weight value of the candidate. Application of Decision Support Systems Scholarship Reception is built using the programming language PHP (Hypertext Preprocessor) and MySQL database.